Aliphatic polycarbonate resin, aliphatic polycarbonate resin crosslinked body, and production method of the same

JP2024051732A5Active Publication Date: 2025-02-21LINTEC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022158044
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-02-21
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

Conventional polycarbonate resins, including polyalkylene carbonate resins, exhibit high glass transition temperatures due to their rigid structure, making them unsuitable for applications requiring flexibility and adhesion.

Method used

A novel aliphatic polycarbonate resin is developed with a low glass transition temperature (Tg) by incorporating an ether structure in the main chain and crosslinkable functional groups in the side chains, allowing for flexibility and adhesion through random copolymerization of specific repeating units, and crosslinking using carbon dioxide as a raw material.

Benefits of technology

The resulting aliphatic polycarbonate resin and its crosslinked form exhibit excellent flexibility, tackiness, and cohesive force, making them suitable for adhesives and coatings, while effectively utilizing carbon dioxide as a sustainable raw material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024051732000001
    Figure 2024051732000001
Patent Text Reader

Abstract

To provide a new aliphatic polycarbonate resin and aliphatic polycarbonate resin crosslinked body which contain carbon dioxide as a production raw material and have low glass transition temperatures (Tg), and a new production method of an aliphatic polycarbonate resin crosslinked body which contains carbon dioxide as a production raw material and has a low glass transition temperature (Tg).SOLUTION: An aliphatic polycarbonate resin has such a structure that an ethylene carbonate unit having an ether structure in the main chain and a hydrocarbon group having four or more carbon atoms in the side chain, an ethylene oxide unit having a hydrocarbon group having four or more carbon atoms in the side chain, an ethylene carbonate unit having a crosslinkable functional group in the side chain, and an ethylene oxide unit having a crosslinkable functional group in the side chain are randomly copolymerized.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel aliphatic polycarbonate resin, a crosslinked aliphatic polycarbonate resin, and a method for producing the crosslinked aliphatic polycarbonate resin. [Background technology]

[0002] In recent years, with the growing demand for the creation of a recycling-oriented society, gases such as carbon dioxide, methane, and carbon monoxide have been attracting attention as sustainable carbon raw materials. For example, it has been reported that aliphatic polycarbonates that have only aliphatic (non-aromatic) groups in the main chain can be produced by copolymerizing carbon dioxide and epoxide, and there has been interest in chemical products that use gases such as carbon dioxide as raw materials and their production technologies.

[0003] Carbon dioxide is believed to be a cause of global warming, so effective use of the carbon dioxide emitted from factories during the process of producing various materials contributes to environmental protection.

[0004] Patent Document 1 proposes a polyalkylene carbonate resin containing three types of repeating units obtained by copolymerizing an epoxide compound, a compound having an epoxy group and an acrylate structure, and carbon dioxide in the presence of a heterogeneous catalyst. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2015-533920 Summary of the Invention [Problem to be solved by the invention]

[0006] The invention described in Patent Document 1 aims to provide a polyalkylene carbonate resin that exhibits thermal stability and mechanical properties such as a larger molecular weight and improved strength. Conventional polycarbonate resins, including this polyalkylene carbonate resin, have a high glass transition temperature (Tg) due to the rigidity of the polycarbonate structure. Therefore, they are unsuitable for fields that require flexibility.

[0007] The present invention has been made in view of the above circumstances, and has an object to provide a novel aliphatic polycarbonate resin and crosslinked aliphatic polycarbonate resin having a low glass transition temperature (Tg) which are produced using carbon dioxide as a production raw material, as well as a method for producing a novel crosslinked aliphatic polycarbonate resin having a low glass transition temperature (Tg) which is produced using carbon dioxide as a production raw material. [Means for solving the problem]

[0008] In order to achieve the above object, first, the present invention provides an aliphatic polycarbonate resin having an ether structure in its main chain and a structure in which a repeating unit represented by the following formula (Ia), a repeating unit represented by the following formula (Ib), a repeating unit represented by the following formula (Ic), and a repeating unit represented by the following formula (Id) are randomly copolymerized (Invention 1). [ka] (In formula (Ia) and formula (Ib), R 1 and R 2 are hydrocarbon groups having 4 or more carbon atoms, and may be the same or different. In formula (Ic) and formula (Id), R 3 and R 4 are hydrocarbon groups having a crosslinkable functional group, and may be the same or different.

[0009] In the aliphatic polycarbonate resin according to the above invention (Invention 1), 1 and R 2is a hydrocarbon group having 4 or more carbon atoms, and the relatively long side chain hydrocarbon group lowers the glass transition temperature (Tg), making it suitable for fields requiring flexibility. In addition, the relatively long side chain hydrocarbon group exhibits tackiness, making it particularly suitable as an adhesive. Furthermore, 3 and R 4 Since is a hydrocarbon group having a crosslinkable functional group, crosslinking (preferably self-crosslinking) via the crosslinkable functional group can exhibit good cohesive strength, making it more suitable as a pressure-sensitive adhesive. Furthermore, the aliphatic polycarbonate resin can be produced using carbon dioxide as a production raw material, which allows for effective use of carbon dioxide.

[0010] In the above invention (Invention 1), the crosslinkable functional group is preferably a (meth)acryloyl group or an allyl group (Invention 2).

[0011] In the above inventions (Inventions 1 and 2), 3 Or the above R 4 However, it is preferable that the alkyl group has an alkyl chain (Invention 3).

[0012] In the above inventions (Inventions 1 to 3), the R 3 Or the above R 4 However, it is preferable that the compound has an ether structure (Invention 4).

[0013] In the above inventions (Inventions 1 to 4), the R 3 Or the above R 4 It is preferable that the compound contains a structure represented by the following formula (II) (Invention 5). CH2=CH-C(=O)-OXO- (II) (In formula (II), X is an alkyl chain.)

[0014] In the above inventions (Inventions 1 to 5), the crosslinkable functional group is preferably contained in an amount of 0.01 mol % or more and 10 mol % or less (Invention 6).

[0015] In the above inventions (Inventions 1 to 6), it is preferable that the main chain contains 0.1 mass % or more and 99 mass % or less of the ether structure unit (Invention 7).

[0016] In the above inventions (Inventions 1 to 7), the polymer is preferably a polymerization reaction product of carbon dioxide and an epoxide (Invention 8).

[0017] In the above inventions (Inventions 1 to 8), the glass transition temperature (Tg) is preferably 5° C. or lower (Invention 9).

[0018] Secondly, the present invention provides an aliphatic polycarbonate resin crosslinked product (Invention 10) obtained by crosslinking the aliphatic polycarbonate resin (Inventions 1 to 9).

[0019] In the above invention (Invention 10), the gel fraction is preferably 15% or more and 85% or less (Invention 11).

[0020] In the above inventions (Inventions 10 and 11), it is preferable that the 5% weight loss temperature is 200° C. or higher and 450° C. or lower (Invention 12).

[0021] Thirdly, the present invention provides a method for producing a crosslinked aliphatic polycarbonate resin, comprising irradiating the aliphatic polycarbonate resin (Inventions 1 to 9) with active energy rays to crosslink the aliphatic polycarbonate resin (Invention 13). Effect of the Invention

[0022] According to the present invention, it is possible to provide a novel aliphatic polycarbonate resin and a crosslinked aliphatic polycarbonate resin having a low glass transition temperature (Tg) using carbon dioxide as a raw material. Also, according to the production method of the present invention, it is possible to produce a novel crosslinked aliphatic polycarbonate resin having a low glass transition temperature (Tg) using carbon dioxide as a raw material. [Brief description of the drawings]

[0023] [Figure 1]1 is a chart showing the results of 1H-NMR measurement of the polymer produced in Example 1. [Diagram 2] 1 is a chart showing the results of 1H-NMR measurement of the polymer produced in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an embodiment of the present invention will be described. [Aliphatic polycarbonate resin] An aliphatic polycarbonate resin according to one embodiment of the present invention (hereinafter sometimes referred to as "aliphatic polycarbonate resin A") has an ether structure in its main chain and has a structure in which a repeating unit represented by the following formula (Ia), a repeating unit represented by the following formula (Ib), a repeating unit represented by the following formula (Ic), and a repeating unit represented by the following formula (Id) are randomly copolymerized (hereinafter sometimes referred to as "structure SA"). [ka] (In formula (Ia) and formula (Ib), R 1 and R 2 are hydrocarbon groups having 4 or more carbon atoms, and may be the same or different. In formula (Ic) and formula (Id), R 3 and R 4 are hydrocarbon groups having a crosslinkable functional group, and may be the same or different.

[0025] The aliphatic polycarbonate resin A is R in the above structure SA. 1 and R 2 is a hydrocarbon group having 4 or more carbon atoms, and the relatively long side chain hydrocarbon group results in a low glass transition temperature (Tg). This makes the resin suitable for fields requiring flexibility, and it can be used, for example, as a pressure-sensitive adhesive, adhesive, coating agent, etc. Furthermore, the aliphatic polycarbonate resin A exhibits tackiness due to the relatively long side chain hydrocarbon group, and is therefore suitable as a pressure-sensitive adhesive. Furthermore, the aliphatic polycarbonate resin A is suitable as a pressure-sensitive adhesive, since R in the above structure SA3 and R 4 Since is a hydrocarbon group having a crosslinkable functional group, by crosslinking (preferably self-crosslinking) via the crosslinkable functional group, it can exhibit good cohesive strength, making it more suitable as a pressure-sensitive adhesive.

[0026] As described later, the aliphatic polycarbonate resin A can be produced using carbon dioxide as a production raw material. Therefore, the aliphatic polycarbonate resin A can effectively utilize carbon dioxide during its production.

[0027] R in formula (Ia) and formula (Ib) 1 and R 2 As described above, is a hydrocarbon group having 4 or more carbon atoms. Examples of the hydrocarbon group include an alkyl group and an aryl group such as a phenyl group, and among these, an alkyl group is preferable. The alkyl group preferably has 4 to 20 carbon atoms, more preferably 5 to 18 carbon atoms, particularly preferably 6 to 10 carbon atoms, and further preferably 6 to 9 carbon atoms.

[0028] The alkyl group may be linear, branched, or cyclic, but is preferably linear or branched. Preferred linear alkyl groups include n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, n-decyl, n-undecyl, and n-dodecyl groups, and preferred branched alkyl groups include 2-ethylhexyl and 2-methylpentyl groups. Among these, from the viewpoint of low glass transition temperature (Tg) and tackiness, n-octyl, n-decyl, and n-dodecyl groups are preferred, and n-octyl and n-decyl groups are particularly preferred, with n-octyl being more preferred. The alkyl group may have a substituent.

[0029] Aliphatic polycarbonate resin A contains two or more types of R 1 may contain two or more types of R 2 Also, as described above, R1 and R 2 may be the same or different.

[0030] R in formula (Ic) and formula (Id) 3 and R 4 As described above, is a hydrocarbon group having a crosslinkable functional group. Examples of the crosslinkable functional group include (meth)acryloyl group; alkenyl groups such as allyl group and vinyl group; alkynyl group; alkoxy group, oxy(meth)acryloyl group, etc. Among them, from the viewpoint of self-crosslinking, (meth)acryloyl group or allyl group is preferred, and (meth)acryloyl group is particularly preferred. In this specification, (meth)acryloyl means both acryloyl and methacryloyl. The same applies to other similar terms.

[0031] Above R 3 or R 4 It is preferable that the alkyl chain has an alkyl chain, and in particular, it is preferable that the alkyl chain has a linear alkyl chain. This ensures flexibility even after crosslinking, making the adhesive more suitable. From the viewpoint of such effects, the number of carbon atoms in the alkyl chain is preferably 1 to 20, more preferably 2 to 15, particularly preferably 3 to 10, and further preferably 4 to 8. The alkyl chain may have a substituent.

[0032] Above R 3 or R 4 It is preferable that the aryl group has an ether structure, which can impart flexibility to the resulting aliphatic polycarbonate resin A.

[0033] Above R 3 or R 4 Specifically, it is preferable that the compound contains a structure represented by the following formula (II) or (III): This allows the reaction of the crosslinkable functional group to proceed efficiently, regardless of the length of the alkyl group in the side chain. CH2=CH-C(=O)-OXO- (II) (In formula (II), X is an alkyl chain.) CH2=CH-CH2-YO- (III) (In formula (III), Y is a single bond or an alkyl chain.)

[0034] In addition, the above R 3 or R 4 Specifically, it is particularly preferable that the structure is represented by the following formula (IV) or formula (V). CH2=CH-C(=O)-OXO-CH2- (IV) (In formula (IV), X is an alkyl chain.) CH2=CH-CH2-YO-CH2- (V) (In formula (V), Y is a single bond or an alkyl chain.)

[0035] The number of carbon atoms in the alkyl chain (X) in the above formula (II) and formula (IV) is preferably 1 to 10, more preferably 2 to 8, particularly preferably 3 to 6, and further preferably 4 to 5. The number of carbon atoms in the alkyl chain (Y) in the above formula (III) and formula (V) is preferably 1 to 10, more preferably 1 to 8, particularly preferably 2 to 6, and further preferably 2 to 4.

[0036] Aliphatic polycarbonate resin A contains two or more types of R 3 may contain two or more types of R 4 Also, as described above, R 3 and R 4 may be the same or different.

[0037] The aliphatic polycarbonate resin A has the above-mentioned crosslinkable functional group (R 3 and R 4Preferably, the aliphatic polycarbonate resin A contains 0.01 mol % or more of the crosslinkable functional group, more preferably 0.05 mol % or more, particularly preferably 0.1 mol % or more, and even more preferably 0.3 mol % or more. The aliphatic polycarbonate resin A preferably contains 10 mol % or less of the crosslinkable functional group, more preferably 5 mol % or less, particularly preferably 3 mol % or less, and even more preferably 1 mol % or less. By containing the crosslinkable functional group in the above amount, the aliphatic polycarbonate resin A can form a good crosslinked structure and exhibit a suitable cohesive force as an adhesive.

[0038] The aliphatic polycarbonate resin A preferably contains 0.1 mol% or more of the ether structure unit (the repeating unit represented by formula (Ib) and the repeating unit represented by formula (Id)) in the main chain, more preferably contains 0.5 mol% or more, particularly preferably contains 0.8 mol% or more, and even more preferably contains 1 mol% or more. The aliphatic polycarbonate resin A preferably contains 99 mol% or less of the ether structure unit, more preferably contains 50 mol% or less, particularly preferably contains 20 mol% or less, and even more preferably contains 10 mol% or less. By containing the ether structure unit in the above amount, the aliphatic polycarbonate resin A effectively lowers the glass transition temperature (Tg) and exhibits better tackiness. Note that, when the content ratio of the ether structure unit in the aliphatic polycarbonate resin A increases, the glass transition temperature (Tg) of the aliphatic polycarbonate resin A decreases more, and the tackiness of the adhesive tends to increase.

[0039] The number average molecular weight of the aliphatic polycarbonate resin A is preferably 15,000 or more, more preferably 20,000 or more, particularly preferably 50,000 or more, and even more preferably 80,000 or more. The number average molecular weight of the aliphatic polycarbonate resin A is preferably 2 million or less, more preferably 1 million or less, particularly preferably 500,000 or less, and even more preferably 300,000 or less. When the number average molecular weight of the aliphatic polycarbonate resin A is in the above range, the tackiness becomes better, and the cohesive force after crosslinking also becomes good. The number average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0040] The glass transition temperature (Tg) of the aliphatic polycarbonate resin A is preferably 5° C. or lower, more preferably −10° C. or lower, particularly preferably −20° C. or lower, and further preferably −25° C. or lower. This provides excellent flexibility and better tackiness. The aliphatic polycarbonate resin A has the above-mentioned structure, and thus can achieve the above-mentioned low glass transition temperature (Tg).

[0041] The glass transition temperature (Tg) of the aliphatic polycarbonate resin A is preferably -60°C or higher, more preferably -55°C or higher, particularly preferably -45°C or higher, and even more preferably -40°C or higher. This provides good cohesive strength after crosslinking. The method for measuring the glass transition temperature (Tg) in this specification is as shown in the test examples described later.

[0042] The gel fraction of the aliphatic polycarbonate resin A is preferably 1 to 30%, more preferably 2 to 20%, and even more preferably 4 to 10%. This makes it easier for the gel fraction after crosslinking to fall within the preferred range described below. The method for measuring the gel fraction in this specification is as shown in the test examples described below.

[0043] The 5% weight loss temperature of the aliphatic polycarbonate resin A is preferably 210 to 450° C., particularly preferably 220 to 400° C., and further preferably 230 to 350° C. This makes it easier for the 5% weight loss temperature after crosslinking to fall within the preferred range described later. The method for measuring the 5% weight loss temperature in this specification is as shown in the test examples described later.

[0044] The aliphatic polycarbonate resin A is preferably a polymerization reaction product of carbon dioxide and an epoxide. The aliphatic polycarbonate resin A is preferably a polymerization reaction product of carbon dioxide (CO2) and the R 1 ·R 2 (hereinafter sometimes referred to as "epoxide E1") and R 3 ·R 4 (hereinafter sometimes referred to as "epoxide E2") in the presence of a polymerization catalyst, while controlling the water content to a predetermined amount or less as necessary (see, for example, International Publication No. 2011 / 142259). By selecting an appropriate polymerization catalyst, an ether structure can be introduced into the main chain of the aliphatic polycarbonate resin A. Since carbon dioxide can be used as a raw material for the production of the aliphatic polycarbonate resin A, the carbon dioxide can be effectively utilized.

[0045] The epoxide E1 is not particularly limited as long as it can form the repeating unit represented by formula (Ia) and the repeating unit represented by formula (Ib) in the above-mentioned structure SA through the above-mentioned polymerization reaction, but is preferably a compound represented by the following formula (VI) or a derivative of said compound. In this specification, the term "derivative" refers to a compound in which one or more hydrogen atoms of the original compound are substituted with a group (substituent) other than a hydrogen atom.

[0046] [ka] (In formula (VI), p is an integer of 3 or more.)

[0047] In formula (VI), p is preferably 3-15, more preferably 4-13, particularly preferably 5-11, and further preferably 6-9.

[0048] Specific examples of the epoxide E1 include 1,2-epoxybutane, 1,2-epoxypentane, 1,2-epoxyhexane, 1,2-epoxyheptane, 1,2-epoxyoctane, 1,2-epoxynonane, 1,2-epoxydecane, 1,2-epoxyundecane, and 1,2-epoxydodecane. Among these, from the viewpoint of low glass transition temperature (Tg) and tackiness, 1,2-epoxyhexane, 1,2-epoxyoctane, and 1,2-epoxydecane are preferred, particularly 1,2-epoxyoctane or 1,2-epoxydecane, and more preferably 1,2-epoxydecane. The epoxides listed above may have a substituent.

[0049] The epoxide E2 is not particularly limited as long as it can form a repeating unit represented by formula (Ic) and a repeating unit represented by formula (Id) in the above-mentioned structure SA through the above-mentioned polymerization reaction, but is preferably a compound represented by the following formula (VII) or formula (VIII) or a derivative of said compound.

[0050] [ka]

[0051] [ka]

[0052] CL in formula (VII) and formula (VIII) is a crosslinkable functional group. The crosslinkable functional group can be R 3 and R 4Among them, CL in formula (VII) is preferably a (meth)acryloyl group, and CL in formula (VIII) is preferably an allyl group.

[0053] X in formula (VII) is an alkyl chain. The number of carbon atoms of the alkyl chain is the same as the number of carbon atoms of the alkyl chain (X) in formula (II) and formula (IV) described above. Y in formula (VIII) is a single bond or an alkyl chain. The number of carbon atoms of the alkyl chain is the same as the number of carbon atoms of the alkyl chain (Y) in formula (III) and formula (V) described above.

[0054] Specific examples of the epoxide E2 include 4-hydroxyalkyl (meth)acrylate glycidyl ethers such as 4-hydroxymethyl (meth)acrylate glycidyl ether, 4-hydroxyethyl (meth)acrylate glycidyl ether, 4-hydroxypropyl (meth)acrylate glycidyl ether, 4-hydroxybutyl (meth)acrylate glycidyl ether, 4-hydroxypentyl (meth)acrylate glycidyl ether, and 4-hydroxyhexyl (meth)acrylate glycidyl ether; allyl glycidyl ether; and allyl alkyl glycidyl ether such as allyl methyl glycidyl ether. Among these, from the viewpoint of flexibility after crosslinking and suitability as an adhesive, 4-hydroxybutyl (meth)acrylate glycidyl ether or allyl glycidyl ether is preferred, and 4-hydroxybutyl acrylate glycidyl ether is particularly preferred. The epoxides listed above may have a substituent.

[0055] The epoxide E1 and the epoxide E2 used in the polymerization reaction step may each be one type or two or more types. When two or more types are used, the combination and ratio thereof may be appropriately adjusted depending on the purpose.

[0056] The molar ratio of the epoxide E1 and epoxide E2 used in the polymerization reaction step is preferably 99.99:0.01 to 90:10, more preferably 99.95:0.05 to 95:5, particularly preferably 99.9:0.1 to 99:1, and further preferably 99.7:0.3 to 99.5:0.5.

[0057] The polymerization catalyst used in the production of the aliphatic polycarbonate resin A is not particularly limited as long as it can introduce an ether structure into the main chain of the aliphatic polycarbonate resin A, but specifically, a double metal cyanide complex catalyst (DMC catalyst) is preferred. As the metal in the DMC catalyst, a combination of cobalt and zinc, a combination of cobalt and nickel, or a combination of zinc and nickel is preferred, and among these, a combination of cobalt and zinc is particularly preferred. As the DMC catalyst, Zn3(Co[CN]6)2, Co(Ni[CN]4), Zn(Ni(CN)4), etc. are preferred, and among these, Zn3(Co[CN]6)2 is particularly preferred.

[0058] As described above, the polymerization reaction of the aliphatic polycarbonate resin A is preferably carried out in a pressure vessel. By changing the amount of the polymerization catalyst used in this polymerization reaction, the carbon dioxide pressure, the polymerization temperature, the polymerization time, etc., the content ratio of the ether structural unit in the aliphatic polycarbonate resin A and the molecular weight of the aliphatic polycarbonate resin A can be adjusted.

[0059] The amount of the polymerization catalyst used, for example, in the case of a DMC catalyst, is preferably 0.1 to 15 mg, more preferably 0.1 to 10 mg, and even more preferably 0.1 to 2 mg, per 1 g of epoxy monomer. If the amount of the polymerization catalyst used is reduced, the molecular weight of the aliphatic polycarbonate resin A tends to increase.

[0060] The pressure of carbon dioxide is preferably 0.1 to 10 MPa, more preferably 0.3 to 7.5 MPa, particularly preferably 0.5 to 6 MPa, and further preferably 0.7 to 5 MPa. When the pressure of carbon dioxide is increased, the content ratio of carbonate structural units in the aliphatic polycarbonate resin A tends to increase.

[0061] The amount of carbon dioxide introduced into the aliphatic polycarbonate resin A (CO2 introduction rate) is preferably 10% by mass or more, particularly preferably 15% by mass or more, and further preferably 20% by mass or more. The method for calculating the CO2 introduction rate is as shown in the test examples described later.

[0062] The polymerization temperature is preferably −15 to 95° C., particularly preferably 0 to 75° C., and further preferably 25 to 70° C. By increasing the polymerization temperature, the content ratio of the ether structural unit can be increased and the polymerization time can be shortened.

[0063] The polymerization time is preferably 1 to 48 hours, particularly preferably 2 to 30 hours, and further preferably 5 to 24 hours. If the polymerization time is extended within this range, the molecular weight of the aliphatic polycarbonate resin A tends to increase.

[0064] The polymerization method may be either solution polymerization or bulk polymerization. For example, the solvent (polymerization solvent) used in solution polymerization may be aliphatic hydrocarbons such as hexane, heptane, cyclohexane, etc., aromatic hydrocarbons such as toluene, xylene, etc., halogenated hydrocarbons such as methylene chloride, ethylene chloride, etc., alcohols such as methanol, ethanol, propanol, butanol, 1-methoxy-2-propanol, etc., ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, cyclohexanone, etc., esters such as ethyl acetate, butyl acetate, etc., carbonates such as dimethyl carbonate, ethylene carbonate, etc., and cellosolves such as ethyl cellosolve, etc.

[0065] The above-described aliphatic polycarbonate resin A can be preferably used as a pressure-sensitive adhesive. The pressure-sensitive adhesive may consist of only the aliphatic polycarbonate resin A, or may contain the aliphatic polycarbonate resin A and also contain components other than the aliphatic polycarbonate resin A.

[0066] The adhesive strength of the adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive to stainless steel (SUS304, polished No. 360) is preferably 1 N / 25 mm or more as a lower limit, more preferably 5 N / 25 mm or more, particularly preferably 7 N / 25 mm or more, and even more preferably 10 N / 25 mm or more. On the other hand, the upper limit of the adhesive strength is not particularly limited, but taking into consideration cases where reworkability is required, it is preferably 45 N / 25 mm or less, particularly preferably 40 N / 25 mm or less, and even more preferably 30 N / 25 mm or less.

[0067] The adhesive strength of the adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive to polycarbonate is preferably 3 N / 25 mm or more as a lower limit, more preferably 5 N / 25 mm or more, particularly preferably 7 N / 25 mm or more, and even more preferably 10 N / 25 mm or more. On the other hand, the upper limit of the adhesive strength is not particularly limited, but taking into consideration the need for reworkability, it is preferably 40 N / 25 mm or less, particularly preferably 30 N / 25 mm or less, and even more preferably 25 N / 25 mm or less.

[0068] The adhesive strength of the adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive to polypropylene is preferably 0.1 N / 25 mm or more as a lower limit, more preferably 1 N / 25 mm or more, particularly preferably 3 N / 25 mm or more, and even more preferably 5 N / 25 mm or more. On the other hand, the upper limit of the adhesive strength is not particularly limited, but taking into consideration the need for reworkability, it is preferably 25 N / 25 mm or less, particularly preferably 20 N / 25 mm or less, and even more preferably 15 N / 25 mm or less.

[0069] The specific test method for adhesive strength in this specification is as shown in the test examples described later.

[0070] The holding power (seconds) according to JIS Z0237:2009 of an adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive (adherend is stainless steel (SUS304, polished No. 360), the adhesion area is 25 mm × 25 mm, the temperature during testing is 40°C, a load of 9.8 N is applied, and the time until the adhesive sheet falls (maximum 70,000 seconds)) is preferably 1000 seconds or more, more preferably 2000 seconds or more, particularly preferably 3000 seconds or more, and even more preferably 4000 seconds or more. The specific test method for holding power in this specification is as shown in the test examples described later.

[0071] [Aliphatic polycarbonate resin crosslinked body] The crosslinked aliphatic polycarbonate resin according to one embodiment of the present invention (hereinafter sometimes referred to as "crosslinked aliphatic polycarbonate resin B") is obtained by crosslinking the aliphatic polycarbonate resin A according to the above-mentioned embodiment. The crosslinked aliphatic polycarbonate resin B maintains a low glass transition temperature (Tg) like the aliphatic polycarbonate resin A and exhibits flexibility and tackiness, while its crosslinked structure increases the cohesive force, making it more suitable as an adhesive.

[0072] The crosslinking of the aliphatic polycarbonate resin A may be performed by using a desired crosslinking agent, but is preferably performed by self-crosslinking. That is, the aliphatic polycarbonate resin crosslinked body B according to this embodiment is a crosslinkable functional group (R 3 and R 4 It is preferable that the aliphatic polycarbonate resin A is crosslinked via the crosslinkable functional groups by reacting the aliphatic polycarbonate resins A (crosslinkable functional groups possessed by the aliphatic polycarbonate resin A) with each other.

[0073] The aliphatic polycarbonate resin crosslinked body B can be preferably produced by irradiating an aliphatic polycarbonate resin A with active energy rays. The irradiation with active energy rays causes crosslinkable functional groups in the side chains of the aliphatic polycarbonate resin A to react with each other to form a crosslinked structure.

[0074] Here, the active energy ray refers to an electromagnetic wave or a charged particle ray having an energy quantum, and specific examples thereof include ultraviolet rays, electron beams, etc. Among active energy rays, ultraviolet rays are particularly preferred because they are easy to handle.

[0075] The ultraviolet irradiation can be performed by a high-pressure mercury lamp, an electrodeless lamp, an LED lamp, a xenon lamp, etc., and the amount of ultraviolet irradiation is 50 to 1000 mW / cm illuminance. 2 The light intensity is preferably about 50 to 10,000 mJ / cm. 2 is preferably 80 to 5000 mJ / cm 2 More preferably, it is 200 to 2000 mJ / cm 2 On the other hand, the irradiation with the electron beam can be carried out by an electron beam accelerator or the like, and the irradiation dose of the electron beam is preferably about 10 to 1000 krad.

[0076] When ultraviolet rays are used as the active energy rays for crosslinking the aliphatic polycarbonate resin A, it is preferable to add a photopolymerization initiator to the aliphatic polycarbonate resin A. By adding a photopolymerization initiator in this way, the aliphatic polycarbonate resin A can be crosslinked efficiently, and the crosslinking time and the exposure dose of the active energy rays can be reduced.

[0077] Examples of such photopolymerization initiators include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin-n-butyl ether, benzoin isobutyl ether, acetophenone, dimethylaminoacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, 2-methylanthracene, benzophenone, p-phenylbenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, benzoin ... Examples of the thioxanthraquinone include thoraxanthone, 2-ethyl anthraquinone, 2-tertiary butyl anthraquinone, 2-amino anthraquinone, 2-methyl thioxanthone, 2-ethyl thioxanthone, 2-chloro thioxanthone, 2,4-dimethyl thioxanthone, 2,4-diethyl thioxanthone, benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylamino benzoic acid ester, oligo[2-hydroxy-2-methyl-1[4-(1-methylvinyl)phenyl]propanone], 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and lithium phenyl(2,4,6-trimethylbenzoyl)phosphinate. These may be used alone or in combination of two or more.

[0078] The amount of the photopolymerization initiator is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, particularly preferably 1 part by mass or more, and even more preferably 1.3 parts by mass or more, based on 100 parts by mass of the aliphatic polycarbonate resin A. The amount of the photopolymerization initiator is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, particularly preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less.

[0079] The gel fraction of the aliphatic polycarbonate resin crosslinked body B is preferably 15% or more, more preferably 20% or more, particularly preferably 30% or more, and even more preferably 40% or more. This allows the adhesive to exhibit excellent cohesive strength. The gel fraction is also preferably 85% or less, more preferably 80% or less, particularly preferably 75% or less, and even more preferably 70% or less. This ensures flexibility and maintains good adhesive strength.

[0080] The glass transition temperature (Tg) of the crosslinked aliphatic polycarbonate resin B is preferably 5° C. or lower, more preferably −10° C. or lower, particularly preferably −20° C. or lower, and further preferably −30° C. or lower. This provides excellent flexibility and better tackiness. The crosslinked aliphatic polycarbonate resin B has a structure obtained by crosslinking the aliphatic polycarbonate resin A having the above-mentioned structure, and thus can achieve the above-mentioned low glass transition temperature (Tg).

[0081] The glass transition temperature (Tg) of the crosslinked aliphatic polycarbonate resin B is preferably −60° C. or higher, more preferably −55° C. or higher, particularly preferably −50° C. or higher, and further preferably −45° C. or higher, which leads to better cohesive strength.

[0082] The 5% weight loss temperature of the aliphatic polycarbonate resin crosslinked body B is preferably 200° C. or higher, more preferably 210° C. or higher, particularly preferably 220° C. or higher, and even more preferably 230° C. or higher. This makes the aliphatic polycarbonate resin crosslinked body B excellent in heat resistance and suitable as an adhesive used under high temperatures. The upper limit of the 5% weight loss temperature of the aliphatic polycarbonate resin crosslinked body B is not particularly limited, but is usually preferably 450° C. or lower, more preferably 400° C. or lower, particularly preferably 350° C. or lower, and even more preferably 300° C. or lower.

[0083] The above-described aliphatic polycarbonate resin crosslinked body B can be preferably used as a pressure-sensitive adhesive. The pressure-sensitive adhesive may consist of only the aliphatic polycarbonate resin crosslinked body B, or may contain the aliphatic polycarbonate resin crosslinked body B and a component other than the aliphatic polycarbonate resin crosslinked body B. The pressure-sensitive adhesive may also contain a photopolymerization initiator or a decomposition product thereof.

[0084] The adhesive strength of the adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive to stainless steel (SUS304, polished No. 360) is preferably 1 N / 25 mm or more as a lower limit, more preferably 3 N / 25 mm or more, particularly preferably 5 N / 25 mm or more, and even more preferably 10 N / 25 mm or more. On the other hand, the upper limit of the adhesive strength is not particularly limited, but taking into consideration cases where reworkability is required, it is preferably 30 N / 25 mm or less, particularly preferably 25 N / 25 mm or less, and even more preferably 20 N / 25 mm or less.

[0085] The adhesive strength of the adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive to polycarbonate is preferably 1 N / 25 mm or more as a lower limit, more preferably 2 N / 25 mm or more, particularly preferably 5 N / 25 mm or more, and even more preferably 10 N / 25 mm or more. On the other hand, the upper limit of the adhesive strength is not particularly limited, but taking into consideration the need for reworkability, it is preferably 35 N / 25 mm or less, particularly preferably 30 N / 25 mm or less, and even more preferably 25 N / 25 mm or less.

[0086] The adhesive strength of the adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive to polypropylene is preferably 1 N / 25 mm or more as a lower limit, more preferably 3 N / 25 mm or more, particularly preferably 5 N / 25 mm or more, and even more preferably 7 N / 25 mm or more. On the other hand, the upper limit of the adhesive strength is not particularly limited, but taking into consideration the need for reworkability, it is preferably 25 N / 25 mm or less, particularly preferably 20 N / 25 mm or less, and even more preferably 15 N / 25 mm or less.

[0087] The holding power (seconds) according to JIS Z0237:2009 of an adhesive sheet having an adhesive layer (thickness: 25 μm) made of the above adhesive (adherend is stainless steel (SUS304, polished #360), the attachment area is 25 mm x 25 mm, the test temperature is 40°C, and a load of 9.8 N is applied, and the time until the adhesive sheet falls (maximum 70,000 seconds)) is preferably 8,000 seconds or more, more preferably 10,000 seconds or more, particularly preferably 30,000 seconds or more, and even more preferably 70,000 seconds or more.

[0088] The aliphatic polycarbonate resin A and the crosslinked aliphatic polycarbonate resin B described above can be used as pressure-sensitive adhesives, adhesives, coating agents, etc., due to their flexibility resulting from their low glass transition temperatures (Tg). Furthermore, the aliphatic polycarbonate resin A and the crosslinked aliphatic polycarbonate resin B exhibit tackiness, and can be particularly suitably used as pressure-sensitive adhesives. For example, they can be used for attaching labels to various containers, daily necessities, electric and electronic devices, various machines, medical instruments, etc., and for bonding members together.

[0089] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0091] Example 1 (1) Synthesis of polymerization catalyst 1.33 g of potassium hexacyanocobaltate(III) (K3[Co(CN)6]; Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in 20 mL of deionized water and added dropwise to a vigorously stirred 50°C zinc chloride solution (11.42 g of ZnCl2 dissolved in a mixed solution of 60 mL of deionized water and 30 mL of t-butyl alcohol) over 45 min. The mixture was then vigorously stirred for 60 min. The resulting white suspension was centrifuged at 5000 rpm to isolate a white solid. The isolated white solid was resuspended in a solution of t-butyl alcohol and deionized water (volume ratio of t-butyl alcohol:deionized water = 5:5) with vigorous stirring for 30 min. The isolation and resuspension by centrifugation were then repeated several times while gradually increasing the amount of t-butyl alcohol relative to water (volume ratio of t-butyl alcohol:deionized water was changed from 6:4 to 7:3, 8:2, and 9:1). Finally, the white solid was resuspended in t-butyl alcohol and isolated by centrifugation, and then dried under vacuum at 50 °C to a given mass to obtain the DMC catalyst Zn3(Cо[CN]6)2.

[0092] (2) Polymer synthesis As raw material monomers, 1,2-epoxydecane (Edec; 1,2-decylene oxide) as epoxide E1 and 4-hydroxybutyl acrylate glycidyl ether (4HBAGE; manufactured by Mitsubishi Chemical Corporation) as epoxide E2 were prepared. Then, 1,2-epoxydecane and 4-hydroxybutyl acrylate glycidyl ether were mixed in a ratio (molar ratio) of 99:1, and diluted with 50 parts by mass of toluene (dehydrated toluene (manufactured by Kanto Chemical Co., Ltd., purity confirmed by GC of 99.5% or more)) as a polymerization solvent.

[0093] The raw material monomers (total, excluding the solvent) were added to the pressure vessel in a ratio of 1 mg of the DMC catalyst obtained in (1) above to 1 g of the raw material monomers (total, excluding the solvent). In addition, phenothiazine (manufactured by Tokyo Chemical Industry Co., Ltd., purity confirmed by GC of 99.5% or more) was added as a polymerization inhibitor to a concentration of 200 ppm. Then, the mixture was stirred under an argon atmosphere.

[0094] Next, the inside of the pressure vessel was purged with CO2, and then CO2 was introduced into the pressure vessel by a liquid pump to set the pressure inside the pressure vessel to 4 MPa. Then, the mixture was stirred at 60°C for 18 hours to carry out a polymerization reaction.

[0095] After the reaction was completed, toluene was added to the contents of the pressure vessel to obtain a solution, and the solution was dropped into methanol containing 1M hydrochloric acid to perform reprecipitation purification. The resulting precipitate was collected using filter paper and dissolved in chloroform, after which impurities were removed using a membrane filter (manufactured by Advantec Toyo Co., Ltd., pore size 3.00 μm). The solution was then poured into a Teflon (registered trademark) petri dish and dried in a drying oven at 50° C. for 20 hours to obtain a polymer.

[0096] The structure of the obtained polymer (aliphatic polycarbonate resin) is 1 The results were confirmed by H-NMR (apparatus: Biospin Avance 500, manufactured by Bruker). The chart is shown in FIG. 1. 1 and R 2 is -CH 17 and R 3 and R 4 was -CO-(CH2)4-OC(=O)-CH=CH2.

[0097] Based on the above results, the ratio of ether structural units to carbonate units was estimated from the integral ratio of the corresponding methylene hydrogens. As a result, the ratio (content) of ether structural units in the obtained aliphatic polycarbonate resin was 1.6%, and the ratio (content) of carbonate was 98.4%. The ratio of ether structural units was calculated from the following formula based on α, β, and γ in the chart. Ether structural unit ratio [%] = {γ / (α+β+γ)} × 100

[0098] (3) Manufacturing of adhesive sheets The aliphatic polycarbonate resin obtained above was dissolved in ethyl acetate, and 1.5 parts by mass of 1-hydroxycyclohexyl phenyl ketone as a photopolymerization initiator was added to 100 parts by mass of the aliphatic polycarbonate resin (solid content equivalent; the same applies below), and the mixture was thoroughly stirred to prepare a pressure-sensitive adhesive coating solution.

[0099] The adhesive coating solution was applied by a coater to the release-treated surface of a release sheet (manufactured by Lintec Corporation, product name "SP-PET381031"), one side of which was a polyethylene terephthalate film treated with a silicone-based release agent. The coating layer was then heated at 100°C for 1 minute to form an adhesive layer with a thickness of 25 μm. Next, the adhesive layer on the release sheet was bonded to a polyethylene terephthalate film (manufactured by Toyobo Co., Ltd., product name "Cosmoshine A4360", thickness 50 μm) as a substrate, and this was used as an adhesive sheet (before UV).

[0100] The thickness of the pressure-sensitive adhesive layer is a value measured in accordance with JIS K7130 using a constant pressure thickness measuring device (manufactured by Techclock Corporation, product name "PG-02").

[0101] Next, the pressure-sensitive adhesive sheet was irradiated with active energy rays through the release sheet under the following conditions to crosslink the pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer after crosslinking was made of a crosslinked aliphatic polycarbonate resin. The pressure-sensitive adhesive sheet having the pressure-sensitive adhesive layer after crosslinking is called pressure-sensitive adhesive sheet (after UV).

[0102] <Activated energy ray irradiation conditions> -High pressure mercury lamp used ·Illuminance 200mW / cm 2 , light intensity 1800mJ / cm 2 The UV illuminance and light intensity meter used is the UVPF-A1 manufactured by iGraphics Co., Ltd.

[0103] [Examples 2 to 6] Polymers and adhesive sheets were produced in the same manner as in Example 1, except that the mixing ratio (molar ratio) of 1,2-epoxydecane and 4-hydroxybutyl acrylate glycidyl ether was changed to 99.5:0.5 (Example 2), 99.7:0.3 (Example 3), 99.9:0.1 (Example 4), 99.5:0.5 (bulk polymerization without using a polymerization solvent, CO2 pressure: 1 MPa) (Example 5), and 99.5:0.5 (CO2 pressure: 1 MPa) (Example 6).

[0104] The structure of the obtained polymer (aliphatic polycarbonate resin) is 1 The results were confirmed by H-NMR (apparatus: Bruker Biospin Avance 500). The ratio of the ether structural unit and the carbonate ratio in the aliphatic polycarbonate resin are shown in Table 1.

[0105] [Examples 7 to 10] As raw material monomers, 1,2-epoxyoctane (Eoct; 1,2-octylene oxide) as epoxide E1 and 4-hydroxybutyl acrylate glycidyl ether (4HBAGE; manufactured by Mitsubishi Chemical Corporation) as epoxide E2 were prepared. Then, 1,2-epoxyoctane and 4-hydroxybutyl acrylate glycidyl ether were mixed in the following ratios (molar ratio): 99.9:0.1 (Example 7), 99.7:0.3 (Example 8), 99.5:0.5 (Example 9), and 99:1 (Example 10).

[0106] A polymer and a pressure-sensitive adhesive sheet were produced in the same manner as in Example 1, except that the raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. The structure of the resulting polymer (aliphatic polycarbonate resin) is as follows: 1 The results were confirmed by H-NMR (apparatus: Bruker Biospin Avance 500). The ratio of the ether structural unit and the carbonate ratio in the aliphatic polycarbonate resin are shown in Table 1.

[0107] [Examples 11 and 12] As raw material monomers, 1,2-epoxyoctane (Eoct; 1,2-octylene oxide) as epoxide E1 and allyl glycidyl ether (AGE) as epoxide E2 were prepared. Then, 1,2-epoxyoctane and allyl glycidyl ether were mixed in a ratio (molar ratio) of 99:1 (Example 11) and 90:10 (Example 12).

[0108] A polymer and a pressure-sensitive adhesive sheet were produced in the same manner as in Example 1, except that the raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. The structure of the obtained polymer (aliphatic polycarbonate resin) is as follows: 1 The results were confirmed by H-NMR (apparatus: Bruker Biospin Avance 500). The ratio of the ether structural unit and the carbonate ratio in the aliphatic polycarbonate resin are shown in Table 1.

[0109] Example 13 As raw material monomers, 1,2-epoxydecane (Edec; 1,2-decylene oxide) as epoxide E1 and allyl glycidyl ether (AGE) as epoxide E2 were prepared. 1,2-epoxyoctane and allyl glycidyl ether were mixed in a molar ratio of 99:10.

[0110] A polymer and a pressure-sensitive adhesive sheet were produced in the same manner as in Example 1, except that the raw material monomers were used and bulk polymerization was performed without using a polymerization solvent. The structure of the obtained polymer (aliphatic polycarbonate resin) is as follows: 1 The results were confirmed by H-NMR (apparatus: Bruker Biospin Avance 500). The ratio of the ether structural unit and the carbonate ratio in the aliphatic polycarbonate resin are shown in Table 1.

[0111] Comparative Example 1 (1) Synthesis of polymerization catalyst (R,R)-N,N'-bis(3,5-di-tert-butylsalicylidene)-1,2-diaminocyclohexanecobalt(II) (Sigma-Aldrich Japan, LLC, product name "(R,R)-salcyCoII") and pentafluorobenzoic acid (Tokyo Chemical Industry Co., Ltd.) were weighed out to a molar ratio of 1:1.1 and placed in a flask, to which was added dehydrated toluene. The flask was then shielded from light with aluminum foil and reacted at room temperature for 20 hours. After completion of the reaction, the solvent was removed under reduced pressure and the mixture was washed several times with an excess amount of hexane. The mixture was then vacuum dried at room temperature to obtain a cobalt salen complex.

[0112] (2) Polymer synthesis 1,2-epoxypropane (propylene oxide; PO) (classified as epoxide E1 for convenience) as an epoxy monomer, the cobalt salen complex obtained in (1) above as a polymerization catalyst, and bis(triphenylphosphoranylidene)ammonium chloride (PPNCl) as a cocatalyst were weighed out in a molar ratio of epoxy monomer:polymerization catalyst:cocatalyst=2000:1:1, and stirred in a pressure vessel. All of these operations were carried out with the pressure vessel replaced with an argon atmosphere. In this polymerization process, no polymerization solvent was used, and bulk polymerization was carried out.

[0113] Next, the inside of the pressure vessel was purged with CO2, and then CO2 was introduced into the pressure vessel by a liquid pump to set the pressure inside the pressure vessel to 1.5 MPa. Then, the mixture was stirred at 23°C for 5 hours to carry out a polymerization reaction.

[0114] After the reaction was completed, chloroform was added to the contents of the pressure vessel to prepare a chloroform solution, which was then concentrated using a rotary evaporator. The concentrated solution was dropped into methanol containing 1M hydrochloric acid while stirring to precipitate the product. The product was then recovered by vacuum filtration using a diaphragm pump. The recovered product was dissolved again in chloroform, and impurities were removed using a membrane filter (manufactured by Advantec Toyo Co., Ltd., pore size 3.00 μm). The solution was then poured into a Teflon (registered trademark) petri dish and dried in a drying oven at 50° C. for 20 hours to obtain a polymer. The structure of this polymer (aliphatic polycarbonate resin; side chain carbon number 1) is as follows: 1 The analysis was performed using H-NMR (apparatus: Bruker Biospin Avance 500). The resulting chart is shown in FIG.

[0115] Based on the above results, the ratio of carbonate units to ether structural units was estimated from the integral ratio of the corresponding methylene hydrogens. As a result, since no γ peak was observed, the ratio (content; mass basis) of ether structural units in the obtained aliphatic polycarbonate resin was 0.0%.

[0116] (3) Manufacturing of adhesive sheets The aliphatic polycarbonate resin obtained above was used to produce an adhesive sheet in the same manner as in Example 1. The adhesive layer of the obtained adhesive sheet had no tackiness, and the adhesive strength and holding power could not be measured.

[0117] Comparative Example 2 As raw material monomers, 1,2-epoxypropane (propylene oxide; PO) (classified as epoxide E1 for convenience) and 4-hydroxybutyl acrylate glycidyl ether (4HBAGE; manufactured by Mitsubishi Chemical Corporation) as epoxide E2 were prepared. Then, 1,2-epoxypropane and 4-hydroxybutyl acrylate glycidyl ether were mixed in a ratio (mass ratio) of 90:10.

[0118] The same polymer preparation procedure as in Example 1 was carried out, except that the above-mentioned raw material monomers were used and bulk polymerization was carried out without using a polymerization solvent. However, gelation occurred, and it was not possible to obtain a polymer whose physical properties could be measured.

[0119] [Test Example 1] <Measurement of number average molecular weight (Mn)> The number average molecular weight (Mn) of the aliphatic polycarbonate resins prepared in the Examples and Comparative Examples was measured by gel permeation chromatography (GPC) under the following conditions (GPC measurement) and converted into standard polystyrene. The results are shown in Table 1. [Measurement conditions] GPC measuring device: Tosoh Corporation, HLC-8320 GPC columns (passed in the following order): Tosoh Corporation TSK guard column SuperH-H TSK gel SuperHM-H TSK gel SuperHM-H TSK gel SuperH2000 Measurement solvent: Tetrahydrofuran ·Measurement temperature: 40℃

[0120] [Test Example 2] <Measurement of glass transition temperature (Tg)> The aliphatic polycarbonate resin (before UV) prepared in the examples and comparative examples and the aliphatic polycarbonate crosslinked body (after UV) constituting the adhesive layer of the adhesive sheet (after UV) produced in the examples were measured using a differential scanning calorimeter (manufactured by TA Instruments Japan, product name "DSC Q2000") to determine the glass transition temperature (Tg). Specifically, 4 mg of a polymer sample was taken and placed in an aluminum pan, which was then sealed with a lid. The measurement was performed by heating and cooling the sample at a temperature increase and decrease rate of 10°C / min in the range of -70°C to 70°C under a dry nitrogen atmosphere. Among the obtained data, a DSC curve was created using the data from the 2nd heating. The temperature at the intersection of the straight line extending the low-temperature side baseline of the obtained DSC curve to the high-temperature side and the tangent line drawn at the point where the gradient of the curve of the stepwise change part of the glass transition is maximum was taken as the glass transition temperature (Tg). The results are shown in Table 1.

[0121] [Test Example 3] <Measurement of gel fraction> The adhesive sheets (before UV) and the adhesive sheets (after UV) produced in the examples and comparative examples were cut to a size of 80 mm x 80 mm, the adhesive layer was wrapped in a polyester mesh (mesh size 200), and the mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated M1.

[0122] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 72 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. The mass at this time was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The gel fraction (%) of each adhesive (aliphatic polycarbonate resin (before UV) and aliphatic polycarbonate resin crosslinked body (after UV)) was derived from this. The results are shown in Table 1.

[0123] [Test Example 4] <Measurement of 5% weight loss temperature> The aliphatic polycarbonate resin (before UV) prepared in the examples and comparative examples, and the aliphatic polycarbonate resin crosslinked body (after UV) constituting the adhesive layer of the adhesive sheet (after UV) produced in the examples were subjected to thermogravimetry using a differential thermal and thermogravimetry simultaneous analyzer (manufactured by Shimadzu Corporation, product name "DTG-60"), with nitrogen as the inflow gas, a gas inflow rate of 100 ml / min, and a temperature rise rate of 20°C / min, while heating from 40°C to 550°C (based on JIS K7120 "Method of thermogravimetry of plastics"). Based on the obtained thermogravimetry curve, the temperature at which the mass is reduced by 5% relative to the mass at a temperature of 100°C (5% weight reduction temperature) was determined. The results are shown in Table 1.

[0124] [Test Example 5] <Measurement of adhesive strength> The adhesive sheets (before UV) and the adhesive sheets (after UV) produced in the examples and comparative examples were cut to a width of 25 mm and a length of 300 mm. In an environment of 23°C and 50% RH, the release sheet was peeled off from the adhesive sheet, and the exposed adhesive layer was attached to the following three types of adherends. When attaching, the adhesive sheet was pressed against the adherend by moving a roller weighing 2 kg back and forth once. After that, the samples were left for 24 hours in an environment of 23°C and 50% RH to be used as samples for measuring adhesive strength.

[0125] Next, in an environment of 23°C and 50% RH, a tensile tester (manufactured by Orientec Co., Ltd., product name "Tensilon") was used to measure the adhesive strength (N / 25mm) when the laminate of the base film and the adhesive layer in the adhesive strength measurement sample was peeled off from the adherend under the conditions of a peel speed of 300mm / min and a peel angle of 180°. The measurements were performed under conditions other than those described here in accordance with JIS Z0237:2000. The results are shown in Table 1. Note that in the adhesive sheet (before UV) of Example 1, the adherend polypropylene (PP) plate experienced zipping, so there was a range in the adhesive strength. Therefore, the average maximum value and the average minimum value were read as the adhesive strength value.

[0126] <Adherend> · Stainless steel (SUS) plate (SUS304, #360 finish) · Polycarbonate (PC) plate (manufactured by Yuko Kogyo Co., Ltd., product name "PC (PC-1600)", thickness: 2 mm) · Polypropylene (PP) plate (manufactured by Yuko Kogyo Co., Ltd., product name "PP (PP-N-BN)", thickness: 2 mm)

[0127] Note that "G", "Cf", and "Zip" in the "Adhesion" column of Table 1 have the following meanings respectively. G: A faint trace remained on the adherend surface. Cf: Cohesive failure of the adhesive layer was observed. Zip: Zipping occurred.

[0128] 〔Test Example 6〕<Measurement of Holding Power> The adhesive layers of the pressure-sensitive adhesive sheets (before UV) and pressure-sensitive adhesive sheets (after UV) manufactured in the examples and comparative examples were attached to a stainless steel (SUS) plate (SUS304, #360 finish) as the adherend. At this time, the attachment area of the adhesive layer to the stainless steel plate was made to be 25 mm × 25 mm in size. In this way, the stainless steel plate with the pressure-sensitive adhesive sheet attached was left standing in an environment of 23°C and 50% RH for 15 minutes, then set in a creep tester, and left standing in this state for another 15 minutes. Next, a load of 9.8 N was applied to the pressure-sensitive adhesive sheet in an environment of 40°C, and the time until the pressure-sensitive adhesive sheet fell (maximum 70,000 seconds) was measured according to the measurement method of the holding power of JIS Z0237:2009, and the holding power (seconds) of the adhesive layer was obtained. The results are shown in Table 1.

[0129] Note that "N.C." and "Cf" in the "Holding Power" column of Table 1 have the following meanings respectively. N.C.: Not only did the pressure-sensitive adhesive sheet not fall even after exceeding 70,000 seconds during the measurement of the holding power, but also no displacement occurred at the attachment position of the pressure-sensitive adhesive sheet to the adherend. Cf: Cohesive failure of the adhesive layer was observed.

[0130] 〔Test Example 7〕<Calculation of CO2 Introduction Rate> The CO2 introduction rate (mass%) in the aliphatic polycarbonate resin (polymer) prepared in the examples and comparative examples was calculated based on the following formula. It can be said that the higher the CO2 introduction rate, the more effectively carbon dioxide is used. The results are shown in Table 1. CO2 introduction rate [mass%] = (Amount of CO2 in polymer [g] / Amount of polymer [g]) × 100 Amount of CO2 in polymer [g] = 44 × (carbonate ratio [%]) Amount of polymer [g] = {(unit molecular weight of carbonate moiety in polymer) × (carbonate ratio [%])} + {(unit molecular weight of ether moiety in polymer) × (ether structural unit ratio [%])} Carbonate ratio [%] = 100 - Ether structural unit ratio [%]

[0131] [Table 1]

[0132] As can be seen from Table 1, the aliphatic polycarbonate resin of the example (before UV) was produced using carbon dioxide as a raw material, had a low glass transition temperature (Tg), and was usable as an adhesive. The aliphatic polycarbonate resin crosslinked body of the example (after UV) was produced using carbon dioxide as a raw material, had a low glass transition temperature (Tg), and was suitable as an adhesive. [Industrial Applicability]

[0133] The aliphatic polycarbonate resin and the crosslinked aliphatic polycarbonate resin according to the present invention can be suitably used as an adhesive or the like.

Claims

1. An aliphatic polycarbonate resin having an ether structure in its main chain, and a structure in which a repeating unit represented by the following formula (Ia), a repeating unit represented by the following formula (Ib), a repeating unit represented by the following formula (Ic), and a repeating unit represented by the following formula (Id) are randomly copolymerized: 【Chemistry 1】 (In formula (Ia) and formula (Ib), R 1 and R 2 are hydrocarbon groups having 6 or more carbon atoms, and may be the same or different. 3 and R 4 are hydrocarbon groups having a crosslinkable functional group, and may be the same or different.

2. 2. The aliphatic polycarbonate resin according to claim 1, wherein the crosslinkable functional group is a (meth)acryloyl group or an allyl group.

3. The R 3 Or the above R 4 The aliphatic polycarbonate resin according to claim 1, characterized in that it has an alkyl chain.

4. The R 3 Or the above R 4 The aliphatic polycarbonate resin according to claim 1, characterized in that it has an ether structure.

5. The R 3 Or the above R 4 The aliphatic polycarbonate resin according to claim 1, characterized in that it contains a structure represented by the following formula (II): CH 2 =CH-C(=O)-O-X-O- ・・・(II) (In formula (II), X is an alkyl chain.)

6. 2. The aliphatic polycarbonate resin according to claim 1, comprising the crosslinkable functional group in an amount of 0.01 mol % or more and 10 mol % or less.

7. 2. The aliphatic polycarbonate resin according to claim 1, wherein the main chain contains 0.1 mass % or more and 99 mass % or less of the ether structure unit.

8. 2. The aliphatic polycarbonate resin according to claim 1, which is a polymerization reaction product of carbon dioxide and an epoxide.

9. 2. The aliphatic polycarbonate resin according to claim 1, which has a glass transition temperature (Tg) of 5° C. or lower.

10. An aliphatic polycarbonate resin crosslinked product obtained by crosslinking the aliphatic polycarbonate resin according to any one of claims 1 to 9.

11. 11. The aliphatic polycarbonate resin crosslinked product according to claim 10, characterized in that the gel fraction is 15% or more and 85% or less.

12. 11. The aliphatic polycarbonate resin crosslinked product according to claim 10, characterized in that the 5% weight loss temperature is 200° C. or higher and 450° C. or lower.

13. A method for producing a crosslinked aliphatic polycarbonate resin, comprising irradiating the aliphatic polycarbonate resin according to any one of claims 1 to 9 with active energy rays to crosslink the aliphatic polycarbonate resin.